Point-to-point trajectory planning strategy research for a multi-robot towing system - Ll Tao; ZHAO ZhiGang; ZHU MingTong; ZHAO XiangTang (Jixie qiangdu)
In view of the velocity and acceleration discontinuity by lifted object trajectories cannot be directly applied to multi-robot coordination of inverse kinematics problem of the towing system, a inverse kinematic solution strategy based on point-to-point trajectory planning was proposed. Firstly, the kinematic and dynamic model of the system was established, and inverse kinematics of the system were analyzed and different solutions aiming at different situations were given. Secondly, the strategy for solving feasible inverse solution based on point-to-point trajectory planning, and three algebraic programming methods were used to plan the trajectory of lifted objects. The continuity of velocity and acceleration was ensured during the planning process. Finally, the feasibility of the strategy was verified by two simulation examples, and only the quintic polynomial planning method met the tension condition. The research results lay a foundation for the optimal distribution and control of system tension.